(untitled) (Journal of Computational Mathematics, 2001)
In this paper,we discuss the convergence and superconvergence for eigenvalue problem of the biharmonic equation by using the Hermite bicubic element. Based on asymptotic error expansions and interpolation postprocessing, we gain the following estimation: 0 λ_h - λ C_ε h^8-ε where ε＞0 is an arbitrary small positive number and C_ε ＞0 is a constant.